Cost Effective Maintenance and Machine Reliability for Food Manufacturing Industries using Optimal Maintenance Strategy - , Igbokwe Nkemakonam, C. Godwin Harold (Archives of Current Research International, 2022)
An optimal maintenance strategy for cost effective maintenance and machine reliability in food manufacturing industries was developed in this study. Maintenance and cost parameters were employed to develop cost-reliability based model in terms of an optimal maintenance using lingo solver. The developed cost-reliabilitybased model considered system’s reliability, cost of equipment failure, preventive maintenance, corrective maintenance and downtime cost associated with - equipment maintenance. A case of a food manufacturing company in Nigeria was observed and the data wasused to evaluate the model. It is imperative to know that, the developed optimal maintenance strategy provided better cost savings and improved system reliability than the current maintenance cost and machine reliability of the industrial case study.